The IT Measurement Compendium - Bundschuh, Manfred (Springer, 2017)
The first step towards success in a software project is to ensure a professional setup. This includes a metrics-based formal estimation process to ensure a solid foundation for project planning. Accurate estimates require quantitative measurements, ideally tool based. In addition, software project managers must also monitor and update these estimates during the project’s lifecycle to control progress and assess possible risks.